Four Problems on Ratio and Proportion With Their Solutions - Maitra, S N (SCHOOL SCIENCE, 2021)
Three jars respectively contain three different liquids whose weights are in some ratio. Three different powders each are mixed respectively with the liquids. Knowing the total weight of the liquids, that of the powders and that of the blended liquids, weights of the individual liquids and powders are determined. Another problem of ratio and proportion related to velocities of a train is set forth and solved. Finally two more problems of ratio and proportion pertaining to weights and price rates of three commodities are incorporated with their solutions.